Product market regulation, business churning and productivity: Evidence from the European Union countries - Bob Anderton; Benedetta Di Lupidio; Barbara Jarmulska (European Central Bank (ECB), 2019)
Productivity performance in European countries has been a policy concern for some time. This paper shows that productivity can be enhanced by product market policies which, by increasing competition and efficiency, facilitate higher rates of firms' entry and exit (i.e., firm churning). Drawing on annual country-sector data for the period 2000-2014 across the EU countries, we find that: (i) competition-enhancing regulation is associated with a higher rate of firm churning; (ii) business churning, in turn, appears to be positively related to higher total factor productivity at the sector level by facilitating the entry of new competitive firms and the exit of less productive ones. Overall, we conclude that stringent product market regulation can be indirectly associated, via its impact on business dynamism, with the somewhat weak productivity performance in a number of EU countries. Thus, our results point towards significant productivity gains that could follow from the introduction of further competition-enhancing measures in product markets.
Keywords: L51; P23; D21; D24; O40; 330; Regulation; Product Market; Creative Destruction; Total Factor Productivity; Growth